La transformation des normes professionnelles de personnel de direction en contexte d’incertitude : étude de cas dans deux établissements au profil contrasté - Jean-Luc Denny (Éducation et Socialisation)
The closure of schools in the spring of 2020 linked to the health crisis, combined with the maintenance of the right to education, implies the establishment of pedagogical continuity. The article proposes to explore its application by studying its effects on the professional norms of executives of educational institutions (Perdir)1. The path proceeds from the ergological approach, the professional practice is approached from an anthropological point of view on the work granting a heuristic function to its study. The research data is based on interviews conducted with two Perdir a few days before the second confinement in France. The results show a changed relationship with teachers and families, an experience of isolation from the supervisory authorities, and management practices qualified as skilled.